2007
DOI: 10.1177/0959683607082556
|View full text |Cite
|
Sign up to set email alerts
|

Episodic struvite deposits in a Northern Great Plains flyway lake: indicators of mid-Holocene drought?

Abstract: A series of 34 layers of struvite (hydrous Mg-ammonium-phosphate) were deposited in laminated sediments of Kettle Lake, North Dakota, in the Northern Great Plains, USA. Sedimentologic, mineralogic and nitrogen isotopic evidence suggest that struvite was deposited during nutrient-enriched eutrophication events within a Mg-rich lacustrine environment. The struvite layers are dispersed between 4650 and 8700 cal. yr BP, with particularly high frequency between 8068 and 8700 cal. yr BP. The youngest struvite layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…The relatively high permeability of the surrounding substratum gives the lake a strong connection with groundwater, and Kettle Lake is a flowthrough groundwaterdominated lake. Indeed, the chemistry of the lake is not significantly different from the relatively fresh groundwater (1.2 g/l) of the Little Muddy Aquifer (Donovan and Grimm, 2007). Because of this strong connection with ground water, the salinity of Kettle Lake (0.8 g/l) is somewhat anoma lous in a region where lakewater chemistries are strongly driven by evaporative losses (Last, 1993).…”
Section: Site Descriptionmentioning
confidence: 97%
See 2 more Smart Citations
“…The relatively high permeability of the surrounding substratum gives the lake a strong connection with groundwater, and Kettle Lake is a flowthrough groundwaterdominated lake. Indeed, the chemistry of the lake is not significantly different from the relatively fresh groundwater (1.2 g/l) of the Little Muddy Aquifer (Donovan and Grimm, 2007). Because of this strong connection with ground water, the salinity of Kettle Lake (0.8 g/l) is somewhat anoma lous in a region where lakewater chemistries are strongly driven by evaporative losses (Last, 1993).…”
Section: Site Descriptionmentioning
confidence: 97%
“…The two cores were aligned strati graphically and a composite continuous sedimentary sequence 21.87 m in length was developed (Donovan and Grimm, 2007;Grimm et al, 2011). While laminations are present throughout the core, they are not consistently annual and cannot be used for varve chronology.…”
Section: Core Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). Struvite is observed in freshwater sediments (Cohen and Ribbe, 1966;Donovan and Grimm, 2007;Pi et al, 2010), and porewater saturation calculations indicate that struvite might also be present in some brackish-marine systems (e.g., Kau Bay and Saanich Inlet; Middelburg, 1990;Murray et al, 1978). In order for struvite to precipitate, porewaters need to be elevated in NH + 4 and PO 4 and have high molar Mg / Ca porewater ratios (e.g., above 580 mol mol −1 by pH 7.6-7.9 and a PO 4 concentration of 10 µM; Gull and Pasek, 2013), conditions that are not met in the Bornholm Basin (Fig.…”
Section: +3000 Yearsmentioning
confidence: 99%
“…In turn, information on sedimentation processes may allow for inferences of key environment changes in the past, e.g. floods, earthquakes, fire, or human reclamation events (Arnaud et al, 2002;Moreno et al, 2008) and although sediment disturbances can be disadvantageous, numerous palaeolimnological studies have revealed that a reasonable chronology can be achieved, especially where multicore comparisons allow sediment disturbances to be distinguished (Tibby 2001;Donovan and Grimm, 2007;Morellón et al, 2011).…”
mentioning
confidence: 99%